Effect the accumulation of bioactive constituents of a medicinal plant (Salvia Miltiorrhiza Bge.) by arbuscular mycorrhizal fungi community - Wu, Yan-Hong; Qin, Yong; Cai, Qing-Qing; Liu, Min; He, Dong-Mei; Chen, Xin; Wang, Hai; Yan, Zhu-Yun (BMC plant biology, 2023)
Arbuscular mycorrhizal fungi (AMF) form symbiotic relationships with various terrestrial plants and have attracted considerable interest as biofertilizers for improving the quality and yield of medicinal plants. Despite the widespread distribution of AMFs in Salvia miltiorrhiza Bunge's roots, research on the impact of multiple AMFs on biomass and active ingredient accumulations has not been conducted. In this study, the effects of five native AMFs (Glomus formosanum, Septoglomus constrictum, Rhizophagus manihotis, Acaulospora laevis, and Ambispora gerdemannii) and twenty-six communities on the root biomass and active ingredient concentrations of S. miltiorrhiza were assessed using the total factor design method. Thirty-one treatment groups formed symbiotic relationships with S. miltiorrhiza based on the pot culture results, and the colonization rate ranged from 54.83% to 89.97%. AMF communities had higher colonization rates and total phenolic acid concentration than single AMF, and communities also appeared to have higher root fresh weight, dry weight, and total phenolic acid concentration than single inoculations. As AMF richness increased, there was a rising trend in root biomass and total tanshinone accumulations (ATTS), while total phenolic acid accumulations (ATP) showed a decreasing trend. This suggests that plant productivity was influenced by the AMF richness, with higher inoculation benefits observed when the communities contained three or four AMFs. Additionally, the affinities of AMF members were also connected to plant productivity. The inoculation effect of closely related AMFs within the same family, such as G. formosanum, S. constrictum, and R. manihotis, consistently yielded lower than that of mono-inoculation when any combinations were applied. The co-inoculation of S. miltiorrhiza with nearby or distant AMFs from two families, such as G. formosanum, R. manihotis, and Ac. laevis or Am. gerdemannii resulted in an increase of ATP and ATTS by more than 50%. AMF communities appear to be more beneficial to the yield of bioactive constituents than the single AMF, but overall community inoculation effects are related to the composition of AMFs and the relationship between members. This study reveals that the AMF community has great potential to improve the productivity and the accumulation of bioactive constituents in S. miltiorrhiza, indicating that it is an effective way to achieve sustainable agricultural development through using the AMF community.